Evaluation of rate of fluoride release from orthodontic bonding materials containing fluoride - An in vitro study - Sangeetha Duraisamy; W S Manjula; L Muthusamy; G Vimala (Wolters Kluwer Medknow Publications, 2012)
The efficacy of an orthodontic bonding material containing fluoridein preventing enamel decalcification around orthodontic brackets depends on the amount of fluoride released by the material. Aim: The purpose of the study is to evaluate the amount of fluoride release from two fluoride containing orthodontic bonding materials and to compare it with a composite resin control. Materials and methods: Twenty sample discs were fabricated from each material using a split mold following manufacturer's instruction for curing and stored in distilled water and artificial saliva in an incubator at 37΀C and 100% relative humidity. The amount of fluoride released into the storage medium was measured using a Fluoride ion-specific combination electrode every day in the first week and end of every week for 3 weeks, and again at the end of 30 days. To prevent the cumulative effect the storage media was changed 24 hours before every measurement. Results: Statistically significant differences were found between the fluoride release rates of the three bonding materials evaluated. The resin- modified glass ionomer cement released the maximum amount of fluoride throughout the study both in distilled water and artificial saliva, followed by the polyacid modified composite resin and composite resin. Conclusion: The resin- modified glass ionomer cement and polyacid modified composite resin released sufficient amount of fluoride within the proposed effective range for inhibition of enamel demineralization reported in the literature. Further studies and clinical trials should be conducted to assess the long term benefits and efficiency before recommending these materials as suitable fluoride releasing orthodontic bonding materials.